2009
DOI: 10.1007/s10681-009-0066-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci of acid detergent fiber and grain chemical composition in hulled × hull-less barley population

Abstract: Cultivated barley is the major livestock feed grain in the Northern Plains and Northwestern United States due to the fact that its short growing season and limited rainfall limit the planting and production of corn. Starch and fiber content play a significant role in feedlot performance of animals raised on barley feed. To study the underlying genetic locations and mechanisms for these traits, a recombinant inbred line population was derived from a cross between the hulled barley cultivar Valier and a hullless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 61 publications
0
9
2
Order By: Relevance
“…This is exemplified by the QTL 'Qsch7a', which in a biparental QTL mapping study explained 47% of variation in SC [76]. In the present study, 'QTL23_SC' located in the same genomic region as 'Qsch7a' explains only 0.2% of the variation.…”
Section: Discussioncontrasting
confidence: 47%
“…This is exemplified by the QTL 'Qsch7a', which in a biparental QTL mapping study explained 47% of variation in SC [76]. In the present study, 'QTL23_SC' located in the same genomic region as 'Qsch7a' explains only 0.2% of the variation.…”
Section: Discussioncontrasting
confidence: 47%
“…3) [12]. Marquez-Cedillo et al [8] and Abdel-Haleem et al [14] identified a consensus QTL near the nud locus on chromosome 7HL [8, 14]. However, the location of these QTLs was different from that detected in the present study.…”
Section: Discussioncontrasting
confidence: 79%
“…High starch contents are needed in barley for brewing and feeding (Qi et al ., 2005; Abdel-Haleem et al ., 2010). The phenotype of the starch content was significantly different among the barley germplasm materials, and high-starch content varieties were present within both six-row and two-row barley.…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of markers associated with economically important traits is important for subsequent breeding processes and is thus useful for the community. Previous studies based on linkage mapping (Abdel-Haleem et al ., 2010) and genome-wide association studies (GWAS) (Pasam et al ., 2012) have revealed many molecular markers associated with starch content in barley. However, it is usually expensive and time consuming to assay all individuals collected from a sample population for the target traits.…”
Section: Introductionmentioning
confidence: 99%